Pseudomonas cyclaminis sp. nov., a pathogen causing bacterial bud blight of cyclamen in Japan. Issue 3 (2nd March 2021) - Sawada, Hiroyuki; Fujikawa, Takashi; Osada, Shigeru; Satou, Mamoru
Abstract : Five phytopathogenic bacterial strains, MAFF 301449 T, MAFF 301450, MAFF 301451, MAFF 301452, and MAFF 301453, which were isolated from bud blight lesions of cyclamen ( Cyclamen persicum Mill.) in Miyagi, Japan, were subjected to polyphasic taxonomic characterisation. The cells were Gram-reaction-negative, aerobic, non-spore-forming, motile with one to five polar flagella, and rod-shaped. Analysis of 16S rRNA gene sequences showed that they belong to the genus Pseudomonas, with Pseudomonas extremaustralis 14-3 T (99.79 % sequence similarity), Pseudomonas trivialis DSM 14937 T (99.79 %), Pseudomonas poae DSM 14936 T (99.72 %), and Pseudomonas antarctica CMS 35 T (99.72 %) as their relatives. The genomic DNA G+C content was 60.3 mol% and the major fatty acids (>5 % of the total fatty acids) were C16 : 0, summed feature 3 (C16 : 1  ω7 c /C16 : 1  ω6 c ), summed feature 8 (C18 : 1  ω7 c /C18 : 1  ω6 c ), and C17 : 0 cyclo. Phylogenetic analysis using the rpoD gene sequences and phylogenomic analyses based on the whole genome sequences demonstrated that the strains are members of the Pseudomonas fluorescens subgroup, but form a monophyletic and robust clade separated from their relatives. Average nucleotide identity and digital DNA–DNA hybridisation analyses with the closely related Pseudomonas species corroborated their novel species status. The strains were differentiated from their relatives by phenotypic characteristics, pathogenicity towards cyclamen, cellular fatty acid composition, and whole-cell MALDI-TOF mass spectrometry profiles. Based on the phenotypic, chemotaxonomic, and genotypic data obtained, we conclude that the strains represent a novel Pseudomonas species, for which we propose the name Pseudomonas cyclaminis sp. nov.; the type strain is MAFF 301449 T (=ICMP 23720 T ).